EDITORIAL NOTE: MIGRATIONS AND ICT. SHORT OVERVIEW - Dana DIMINESCU (Studia Universitatis Babeș-Bolyai. Philosophia)
In this introduction, I have taken note of a whole synergy which become established between migrants, given facts, software, devices, territories, that shows evidence of the emergence of a new type of ecological action, a human and non-human assemblage in the migrants life, that cannot be any more interpreted inside the modern political and ideological forms, nor as the result of a technological determinism.